Anthology of modern French song a collection of thirty-nine songs, with piano accompaniment - SPICKER, Max (G. Schirmer. Inc., 1912)
Albayde, A Lucette, Apres un Reve, Ariette, Bonjour Suzon, Brioses d'autrefois,nBeau Doir, Chanson Triste, Chere Buit, La Cloche